2012
DOI: 10.1371/journal.pone.0043832
|View full text |Cite
|
Sign up to set email alerts
|

Text Messaging to Improve Attendance at Post-Operative Clinic Visits after Adult Male Circumcision for HIV Prevention: A Randomized Controlled Trial

Abstract: BackgroundFollowing male circumcision for HIV prevention, a high proportion of men fail to return for their scheduled seven-day post-operative visit. We evaluated the effect of short message service (SMS) text messages on attendance at this important visit.MethodologyWe enrolled 1200 participants >18 years old in a two-arm, parallel, randomized controlled trial at 12 sites in Nyanza province, Kenya. Participants received daily SMS text messages for seven days (n = 600) or usual care (n = 600). The primary outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(122 citation statements)
references
References 19 publications
5
115
1
1
Order By: Relevance
“…By instituting such measures as personal reminders (through technologies such as the now ubiquitous and tested mobile telephony in Kenya; Odeny et al, 2012), socioeconomic incentives (e.g., expanding the food-for-prescription program in Kenya; NACC & NASCOP, 2012), and psychosocial support groups, all aimed at raising the average population retention rate in HIV care, this study shows the feasibility of improved treatment outcomes in PLHIV with better medication adherence as a putative intermediary.…”
Section: Resultsmentioning
confidence: 90%
“…By instituting such measures as personal reminders (through technologies such as the now ubiquitous and tested mobile telephony in Kenya; Odeny et al, 2012), socioeconomic incentives (e.g., expanding the food-for-prescription program in Kenya; NACC & NASCOP, 2012), and psychosocial support groups, all aimed at raising the average population retention rate in HIV care, this study shows the feasibility of improved treatment outcomes in PLHIV with better medication adherence as a putative intermediary.…”
Section: Resultsmentioning
confidence: 90%
“…This suggested that for similar studies in the future, the SMS reminders should be sent out according to the needs of individual patients. Secondly, SMS reminders in the present study were sent daily to patients by one-way communication, However, two-way interactive communication may be more helpful to improve the patients' adherence and interest, as has been suggested by others [31,32]. Thirdly, the study had a limited sample size and a short follow-up period.…”
Section: Discussionmentioning
confidence: 86%
“…One of the more commonly deployed demand-side mHealth interventions is short message service (SMS), or text message, reminders. SMS reminders significantly improve both health-seeking behaviours and outcomes in sub-Saharan Africa6, 7, 8, 9, 10, 11 and immunisation uptake in the USA 12, 13. However, the evidence that these approaches increase immunisation coverage and timeliness in Africa and low-income and middle-income countries (LMICs) is insufficient and has predominantly focused only on timely pentavalent (DTP, Haemophilus influenzae type B [Hib] and Hepatitis B) vaccination 14, 15, 16, 17, 18, 19…”
Section: Introductionmentioning
confidence: 99%